A comparison of surgical techniques in the management of patients with choledocholithiasis undergoing laparoscopic cholecystectomy: an Australian experience - Wong, Pearl; Diab, Jason; Gaszynski, Rafael; Lambrakis, Paul; Apostolou, Christos (International Surgery Journal, 2022)
Background: Optimal management of patients with gallstones and concomitant choledocholithiasis has been a longstanding dilemma. Advancements in laparoscopic and endoscopic techniques have enabled multiple options for management. This study aims to compare the effectiveness of different procedures for choledocholithiasis in patients requiring laparoscopic cholecystectomy in the emergency setting of a large tertiary Australian hospital. Methods: A retrospective review of patients requiring emergency laparoscopic cholecystectomy who were also treated for choledocholithiasis was conducted at Liverpool Hospital, New South Wales. Patients were allocated into three groups: pre-operative endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecyst-ectomy at index admission, or laparoscopic cholecystectomy with intraoperative biliary stent placement followed by interval ERCP and stent removal, or laparoscopic cholecystectomy with intraoperative bile duct exploration. The primary outcome assessed was bile duct clearance rate. The secondary outcomes included complication rates, number of procedures performed, total operative time, length of stay (LOS) and cost. Results: A total of 96 patients were included. Primary outcome was no different between the three groups and there was no significant difference between post-operative complications. However, LOS was shorter in the laparoscopic cholecystectomy with intraoperative bile duct exploration by three days compared to the other two groups. Conclusions: Laparoscopic cholecystectomy with intraoperative bile duct exploration has similar outcomes and complication rates to other techniques and may be associated with a shorter LOS and lower costs.